2023
DOI: 10.1186/s12913-023-09418-3
|View full text |Cite
|
Sign up to set email alerts
|

“More” work for nurses: the ironies of eHealth

Abstract: Background eHealth applications are considered a technological fix that can potentially address some of the grand challenges in healthcare, including burnout among healthcare professionals, the growing burden of patients with chronic conditions, and retaining and recruiting healthcare professionals. However, as the deployment of eHealth applications in healthcare is relatively novel, there is a lack of research on how they affect the work environment of healthcare professionals. This study expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The above also aligns with Torenholt et al (2020), who described that for many cancer patients, the use of PRO forms is a reassuring task and a tool for verification, as the use of PRO responses and the reviewing of data affect the next response, creating a feedback loop [14]. Adopting digital tools for specific processes and improving patient care may result in unintended increased workloads and complexity for the involved health care professionals [20]. Working digitally during the consultation affects the interaction between the cancer survivor and HCPs and provides more invisible work for HCPs as they have to communicate the actions on the screen, complicating the use of body language and eye contact.…”
Section: Invisible Worksupporting
confidence: 66%
See 1 more Smart Citation
“…The above also aligns with Torenholt et al (2020), who described that for many cancer patients, the use of PRO forms is a reassuring task and a tool for verification, as the use of PRO responses and the reviewing of data affect the next response, creating a feedback loop [14]. Adopting digital tools for specific processes and improving patient care may result in unintended increased workloads and complexity for the involved health care professionals [20]. Working digitally during the consultation affects the interaction between the cancer survivor and HCPs and provides more invisible work for HCPs as they have to communicate the actions on the screen, complicating the use of body language and eye contact.…”
Section: Invisible Worksupporting
confidence: 66%
“…Introducing new actors within the workflow of PROs can result in invisible work for the HCPs, as they have to maintain the value of using the PRO forms [14]. Invisible work refers to the work performed behind the scenes and effects of actors that may not be immediately visible or recognized [20]. Implementing PROs can require training and may add additional burdens to existing workflows [21].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated similar challenges with different non-interoperable eHealth solutions that increase HCPs’ workload and are invisible to employers, such as a lack of organizational support and delayed discharge summaries, which cause frustration, fragmented care and jeopardized patient safety, reduced job satisfaction for HCPs, and a lack of sufficient time with patients (Andersen, 2019 ; Bjerkan et al, 2021 ; Fernando & Hughes, 2019 ; Frennert et al, 2023 ; Helse-og omsorgsdepartementet Ministry of Health and Welfare, 2019 ; La Rocca & Hoholm, 2017 ; Mertens et al, 2021 ; Öberg et al, 2018 ). Adding more eHealth solutions is not a solution, as it can lead to HCPs facing digital chaos (Frennert et al, 2023 ; Öberg et al, 2018 ) together with feelings of being overstretched and conflicted between caring touch and task performances and guarding patient safety, and can lead many nurses to leave the profession (Brall et al, 2019 ; Combrinck et al, 2022 ; Frennert et al, 2023 ; Liu et al, 2017 ; Nav, 2023 ). On the other hand, when patient information is up-to-date and available to all HCPs, this ensures patient safety, prevents medical errors, avoids the unnecessary repeating of examinations, and lessens the documentation burden while improving patient symptom management and communication between HCPs and patients (Lehne et al, 2019 ; May et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…eHealth, as part of digital health, refers to technologies used in health fields for secure and cost-effective communication, information management, education, and research ( WHO ). eHealth comprehends different healthcare technological solutions, applications and services, including electronic health records (Frennert et al, 2023 ; Öberg et al, 2018 ). Therefore, this study uses terms eHealth technology, services and eHealth solutions interchangeably, and eHealth when referring to them all as a concept.…”
Section: Introductionmentioning
confidence: 99%
“…Health Education England provides several NHS Digital Academy learning programmes, including a Chief Nursing Information Officer (CNIO) masterclass series and there has been a drive to appoint a chief nursing information officer (CNIO) in every organisation to help support the digital agenda. With respect to health informatics, nursing appears to be further ahead than other professions ( 69 ), perhaps because nurses appear to be taking on the lion's share of responsibility for entering and monitoring digital data ( 70 ). However, digital innovation influences all areas of medicine, nursing and allied health professions and the strong focus to date on health informatics ( 58 ) is not preparing professionals for working in a digitised health and care system ( 71 ).…”
Section: Enablers Of Digital Transformationmentioning
confidence: 99%